Quality of official information about real estate in Iceland - Friðrik Ólafsson 1953- (2011)
In Iceland building a real estate needs design and an approval from authorities before production or change. The design is mainly expressed in drawings and documents, which are also used as a base to communicate between stakeholders of all parts of the project, both tangible and intangible. If the project is not in accordance with these papers, it can lead to misunderstanding about cost, values, price, rights and risk. This quantitative research shows there was difference between approved drawings and documents versus as-built one-family-buildings in Iceland; built 2001-2005 and sold once,2008, and furthermore, valid laws and regulations are not working. The average rating after construction of Conceptual Drawings is 60%, Table of Size and Ownership 55%, Production drawings 51% and of approval of final acceptance is 28%. Drawings and documents are not updated and seldom attached to Purchases Contracts. Gæði opinberra upplýsinga um fasteignir á Íslandi. Á Íslandi er lagaleg krafa um að mannvirki skuli vera hönnuð og samþykkt af yfirvöldum áður en framleiðsla þeirra hefst eða þeim breytt. Hönnun felst aðallega í gerð teikninga og skjala, sem einnig eru notuð sem samskiptagrunnur fyrir aðila er tengjast kunna sérhverjum þætti verks, bæði áþreifanlegum og óáþreifanlegum. Ef mannvirki er ekki í samræmi við gögn, getur það orsakað misskilning er varðar kostnað, verðmæti, verð, réttindi, skyldur og áhættu. Þessi rannsókn sýndi, að munur er á milli samþykktrar gagna af einbýlishúsum og raunveruleikans, það er, mannvirkja sem byggð voru á árunum 2001 til 2005 og seld á árinu 2008, og einnig að gildandi lög og reglugerðir eru ekki að virka. Trúveruleiki upplýsinga er varðar byggingarnefndarteikninga er 60%, skráningartafla 55%, sérmynda 51% og er varðar lokaúttektir 28%. Hönnunargögn eru ekki uppfærð og fylgja sjalda kaupsamningum.